MODEL DISTRIBUSI BAHAN AJAR UNIVERSITAS TERBUKA DAN IMPLEMENTASINYA - Sitta Alief Farihati; Amril Aman; Settings I. N. Kutha Ardana (Jurnal Matematika Sains dan Teknologi, 2009)
Universitas Terbuka (UT) was implementing the centralized distribution of learning material, it is not considered efficient. Therefore, the decentralized distribution system which requires warehouses at certain regional offices will be proposed. The aims of this research are (1) investigating the decentralized learning material distribution model, (2) choosing the optimal location of warehouses to minimize the cost of learning material distribution, (3) choosing the regional offices which will be served optimally by each warehouse, (4) comparing efficiency of the centralized and decentralized learning material distribution system. The distribution problem is modeled as a linear mixed integer programming problem. The model will be solved using Branch and Bound method. This study considers centralized learning material distribution system and two alternative of decentralized learning material distribution systems, which are alternative 1 and alternative 2. It is found that in 2008 the cost of the alternative 2 is lower than the centralized learning distribution system. Besides, if the demand of learning material is increasing, the alternative 2 is still less costly than the other systems.